Architect-activist. The socio-political attitude based on the works of Walter Segal - Gierszon, Mateusz (Journal of Architecture and Urbanism, 2014)
Architecture is a public activity, it is political. This truth is particularly strongly manifested in modern architecture, which through merging with political agenda of a welfare state, has been recognized as a tool for shaping the community, both by improving the standard of housing and disciplining people. In this way, architect has been assigned an important social role. The work attempts to capture a moment in the history of the twentieth century, in which a wave of criticism of modernism led to creating a new paradigm of architecture and a new model of architect: social design and architect-activist. As a model of architect’s attitude might serve the activity of Walter Segal, his socialized designing and model of constructing houses with the use of self-build method. Segal method is interesting because, on the one hand, it is derived from the ideas and achievements of modern architecture, and on the other hand, it creatively forms part of criticicism of modernist building practices. Libertarian and, at the same time, communal aspects of Segal’s methods, together with the ambivalent attitude of the architect, make his work and attitude as co-designer and organiser of the process associated with anarchist idea. Segal method and his attitude of the architect-activist included within it, may be considered as mature model of a modern, strong trend of construction based on the principles of participation and sustainability.